Integrating food security and biodiversity governance: A multi-level social network analysis in Ethiopia. (November 2018) - Jiren, Tolera Senbeto; Bergsten, Arvid; Dorresteijn, Ine; Collier, Neil French; Leventon, Julia; Fischer, Joern
Highlights: Governing food and biodiversity requires cross-sector and cross-level integration. Integration is needed by individual stakeholders and in stakeholder collaborations. Integration both at policy and implementation levels reduce implementation deficit. Stakeholders with formal authority in key positions can link stakeholder groups. Abstract: Integrating food security and biodiversity conservation is an important contemporary challenge. Traditionally, food security and biodiversity conservation have been considered as separate or even incompatible policy goals. However, there is growing recognition of their interdependence, as well as of the need to coordinate solutions across multiple policy sectors and levels of governance. Despite such recognition, there has been no empirical analysis of governance networks that specifically integrates food security and biodiversity. Focusing on southwestern Ethiopia, this paper used social network analysis to investigate three main questions: how stakeholders interact in the governance of food security and biodiversity in a multi-level governance context; how the goals of food security and biodiversity are integrated in such a multi-level governance context; and which stakeholders are popular and play connecting roles between stakeholders in the governance network. The study was conducted in a subsistence dominated farming landscape, where we interviewed 244 stakeholders ranging from local to national levels. We found that the governance of food security and biodiversity conservation was strongly hierarchical, with virtually no horizontal linkages between adjacent districts, and very few vertical direct interactions of stakeholders spanning two or more levels of governance. Introducing a novel analytical distinction of collaborative vs individual integration, we found that only a minority of the collaborations between stakeholders took both food security and biodiversity into account, despite the majority of actors being individually involved in both sectors. Stakeholders with positional power, sociological power (popularity) and formal authority played a liaison role in the governance network. To further improve integration of food security and biodiversity conservation, a governance network that harnesses stakeholder collaboration across sectors and governance levels is essential. However, given the central role of many government administrative organizations, possible problems of power capture by some stakeholders need to be carefully managed.